THE QEDUSEN PROJECT; IMPROVING SENIORS’QUALITY OF LIFE THROUGH TO EDUCATION - Escuder-Mollon, Pilar (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Learning in later life (citizens over 65 or retired) is becoming common. The motivation and interests of the senior citizens to keep learning are mainly personal, they are not job related needs or labour market qualification requirements. These personal aims can be seen from the quality of life (QoL) perspective, where education increases well-being, integration and participation of the elderly in the present society. Institutions dealing with senior learners then face the challenge to provide a socio-educational intervention to senior learners, which has a requirements, needs and motivation different from other adults, and that specific pedagogy, courses and staff qualifications must be considered. From this need the project QEduSen (supported by the Lifelong Learning Programme of the European Commission) produced a guide and a evaluation toolkit